The genus Ophiogomphus Lieftinck, 1964 in Vietnam, with descriptions of the female of O. minimus Karube, 2014 and O. phantoani sp. nov. (Odonata: Gomphidae) - Ngo, Quoc Phu; Nguyen, Minh Ty (Zootaxa, 2021)
Description of Ophiogomphus phantoani sp. nov. (Holotype ♂: Dak Re Commune, Song Thanh National Park, Quang Nam Province, central Vietnam, 15.5080 N, 107.4720 E, altitude 1105 m) is based on both sexes. Three other species of Ophiogomphus in Vietnam are recorded with description of the female O. minimus Karube, 2014 for the first time. Keys to males and females of four species from Vietnam are also provided.